He Authentic Deed Versus the Private Deed in The Case of New Traders Turi Market - Gideon Johanes Suryanda (Fakultas Hukum Universitas Hang Tuah, 2019)
This article discusses about the private deed of the Turi Market’s new developer with Surabaya City Government that can defeat the authentic deed that is owned by new Turi Market traders. The incident began when Turi Market caught fire in 2007, this great fire damage most Turi Market. Many dealers who sell cheap their booth that hasn't burned for venture capital. Traders and shoppers booth could not make transactions normally because the head of Turi Market dismissed, then they had to use a notarial deed in selling booth. Problems arise in 2012 when the Turi Market has finished construction and opened registration for old traders. Notarial deed belong to new traders are not recognized by the developers of the new Turi Market. The trader who has a book registration but the name is different from the owner, then the cost price of the initial regimen prescribed. This led to heavy losses and make the new Turi Market have recently become much quiet. Surabaya City Government should also act to help resolve this problem by creating regional regulations to resolve this issue.